Implikasi Desentralisasi Fiskal dan Tata Kelola Anggaran terhadap Kesejahteraan Masyarakat Melalui Alokasi Anggaran dan Kapasitas Ekonomi: (Studi Kasus Provinsi Sulawesi Barat) - Hardianto Hardianto; Tubagus Ismail; Muhtar Sapiri (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
The implementation of a particular government service or function is no longer dominated by one party (namely the government). This means that the partnership and cooperation process must be further encouraged by reducing the role of government on the one hand, and strengthening the role of the private sector and society on the other hand. The aim of this research is to determine the influence of fiscal decentralization, budget allocation, economic capacity on community welfare, determine the influence of fiscal decentralization on community welfare through budget allocation and economic capacity, determine the influence of budget governance on community welfare through budget allocation and economic capacity in Sulawesi Province West. This research uses a quantitative approach, with a case study of local governments in the West Sulawesi Province which includes six districts. The data collection technique is carried out by document study, using secondary data originating from related agencies or from websites through internet browsing and other documentation. The data analysis technique uses SmartPLS analysis. The findings show that fiscal decentralization has a negative impact on community welfare. Budget governance has a negative influence on community welfare. Budget allocation can influence an increase in community welfare. Economic capacity can improve community welfare. Budget allocation can mediate the effect of fiscal decentralization on community welfare. Economic capacity can mediate the effect of fiscal decentralization on community welfare. Budget allocation cannot mediate the influence of budget governance on community welfare, while economic capacity can mediate the influence of budget governance on community welfare, especially in West Sulawesi Province.